Implementasi Teknologi Energi Surya Sebagai Wujud Mandiri Energi Listrik Di Masjid Al-Falah Serua Ciputat Tangerang Selatan - christine widyastuti; Oktaria handayani; tony koerniawan (Terang, 2020)
The existence of street lighting and or public facilities is one of the things that is very important for the smooth running of residents' activities, especially at night. However, not all of them had lighting installed as in the Al-Falah Serua Ciputat Mosque in South Tangerang. This village is a village that is electrified but electricity supply for public facilities and roads is still minimal, due also to the large cost of using electricity. Therefore it is necessary to install public and street lighting facilities in this case in the form of solar lights as an effective alternative to solutions in lighting and to reduce the cost of using electricity from PLN. The solar lights are very suitable to be installed in this location, considering that the lights do not require electricity from residents' houses and PLN, and geographically the location is very potential for utilizing solar power because it is still very green. Solar lights are installed at strategic points on the road to Al Falah Mosque and the front porch of Al Falah Mosque itself. The lamp used is a HILIOS SL-40W lamp with 40Watt power. In addition to street lighting and public facilities, an economic analysis is also carried out on this activity by comparing the total costs required between incandescent lighting with solar power. Where the nominal difference obtained in rupiah is Rp 311,055.2 lighter than PJU incandescent lamps, and solar lights are not affected by TDL (basic electricity tariff).